Hiking in Rondane wild reindeer range : human trail use and the effect of removing trail marks - Fjelle, Marita (Norwegian University of Life Sciences, Ås, 2020)
Habitat loss caused by human disturbance is one of the largest threats to the wild reindeer (Rangifer tarandus tarandus) in Norway. Increasing infrastructure development and human use of marked trails and tourist cabins in wild reindeer areas are affecting the possibilities for wild reindeer to migrate and leads to separation between populations. Rondane wild reindeer range is probably the area with the most prominent conflicts between human and wild reindeer among the 24 ranges in Norway. To reduce human use in core wild reindeer areas in Rondane and elsewhere, the management have decided to remove problematic hiking trails, including signs, marks, as well as branding of them on maps and brochures. In this thesis I investigated the effect on the human use by removing of five hiking trails in Rondane wild reindeer range. The methods for sampling data of the human use were based on automatic counters, field observations and semi-structured interviews with experts and hikers during the summer of 2019. Two counters were installed on each trail, altogether ten counters, to record the number of hikers. The 2019 counter results were compared with similar pre-data to study if there is a change in human use before and after removal of trail marks. Observations were used to map hiker activity on and off trails, and interviews were used to get local knowledge of the former and today’s use of the five trails. The current human use and effect of removal of hiking trail marks seems to be dependent of location, time since marking removal and user groups. Registrations from counters in 2019 showed relatively low and decreasing use over years. Still, there exist high variation in human use between the trails, and the trail with the highest use had four times as many hikers during the summer as the trail with the lowest use. Change in human use before and after removal of trail marks were tested at one of the trails, but no significant difference was identified. Removal of trail marks on this trail were done less than ten years ago, and it will be likely that it takes some time to see the effects. In addition, visitation to mountains may fluctuate natural from one year to another because of weather conditions etc. The main user group in this study were non-local Norwegian hikers on daytrips, who had visited the trails before. Hikers with knowledge to an area, in addition to local users, are not necessarily available of marked hiking trails and may be difficult to affect by removal of trail marks. M-NF